2004
DOI: 10.1213/01.ane.0000111743.61132.99
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Atelectasis Formation During the Induction of General Anesthesia in Morbidly Obese Patients

Abstract: Application of positive end-expiratory pressure during induction of general anesthesia in morbidly obese patients prevents atelectasis formation and improves oxygenation. Therefore, this technique should be considered for anesthesia induction in morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
124
0
19

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(143 citation statements)
references
References 30 publications
0
124
0
19
Order By: Relevance
“…14 Toutefois, plusieurs manoeuvres comme l'utilisation de PEEP et les méthodes de recrutement alvéolaire peuvent être utilisées pendant l'anesthésie et la ventilation mécanique pour limiter l'étendue de ce problème. 14 De plus, l'atélectasie est plus courante en période postopératoire, et elle dépend principalement de l'hypoventilation postopératoire et de la concentration d'oxygène inspirée à la fin de l'anesthésie. Par conséquent, il n'est pas justifié d'éviter la préoxygénation seulement afin d'éviter l'atélectasie.…”
Section: Atélectasieunclassified
See 1 more Smart Citation
“…14 Toutefois, plusieurs manoeuvres comme l'utilisation de PEEP et les méthodes de recrutement alvéolaire peuvent être utilisées pendant l'anesthésie et la ventilation mécanique pour limiter l'étendue de ce problème. 14 De plus, l'atélectasie est plus courante en période postopératoire, et elle dépend principalement de l'hypoventilation postopératoire et de la concentration d'oxygène inspirée à la fin de l'anesthésie. Par conséquent, il n'est pas justifié d'éviter la préoxygénation seulement afin d'éviter l'atélectasie.…”
Section: Atélectasieunclassified
“…The presence of 100% oxygen in the lungs favours atelectasis due to oxygen uptake from poorly ventilated alveoli. 3,14 When air is present, nitrogen, which is not taken up or consumed, provides a ''splint'' keeping alveoli open. After induction of anesthesia, positive pressure ventilation via a face mask increases DAWD and prevents atelectasis.…”
mentioning
confidence: 99%
“…The use of 10 cm H 2 O continuous positive airway pressure/positive endexpiratory pressure (CPAP/PEEP) throughout the induction period (CPAP when breathing and PEEP after apnea) has been shown to increase the duration of apnea prior to desaturation by 50% in morbidly obese patients. 36,37 Noninvasive positive pressure ventilation using pressure support ventilation with PEEP via a face mask has also been shown to enhance preoxygenation, achieving a more rapid increase and higher end-tidal O 2 when compared with preoxygenation with spontaneous ventilation. 38 …”
Section: Positioning and Preoxygenationmentioning
confidence: 99%
“…Il a été démontré que le recours à une ventilation en pression positive continue / pression positive télé-expiratoire de 10 cm H 2 O (CPAP / PEEP) tout au long de la période d'induction (CPAP lors de la respiration et PEEP après l'apnée) augmentait la durée de l'apnée avant désaturation de 50 % chez les patients obèses morbides. 36,37 En outre, il a également été démontré que la ventilation en pression positive non effractive utilisant une aide inspiratoire et une PEEP via un masque facial améliorait la préoxygénation, résultant en une augmentation plus rapide et un O 2 télé-expiratoire plus élevé comparativement à une préoxygénation en ventilation spontanée. 38 …”
Section: Positionnement Et Préoxygénationunclassified
“…Important limitations of this study were the absence of ventilation between the onset of apnea and intubation, and the relative brevity of the pre-oxygenation (only 3 minutes). Later studies, however, showed a benefi t of applying CPAP with oxygen during pre-oxygenation in morbidly obese patients [18], [19]. Compared to O 2 alone, CPAP of 10 cmH 2 O + O 2 for 5 min increased the time to desaturate and reduced the amount of atelectasis following intubation [18], [19].…”
Section: Non-invasive Ventilation With Positive Pressurementioning
confidence: 99%